MODEL PEMBELAJARAN IMPROVE UNTUK MENINGKATKAN KEMAMPUAN REPRESENTASI MATEMATIS DAN METAKOGNITIF PESERTA DIDIK - Lisna Nur Dina Yanti; Rianti Cahyani (UJMES (Uninus Journal of Mathematics Education and Science), 2019)
This research is motivated by the low mathematical representation ability of students. One alternative learning that can be applied to improve the mathematical representation ability of students is the IMPROVE model. The purpose of the study was to determine the improvement of the mathematical and metacognitive representations of students who learned the IMPROVE and PBL models, as well as the correlation between the ability of mathematical representation to metacognitive students. The method used is quasi-experimental method with nonequivalent control group pretest-posttest design. The sample used by students in class VIII I as an experimental class (30 students) and class VIII J as a control class (32 students) one of the high school in Bandung Regency. The experimental class was treated using the IMPROVE model and the control class with the PBL model. The instrument used is a mathematical representation ability test, metacognitive ability questionnaire, and observation sheet. The results showed that the mathematical representation ability of students with the IMPROVE model was better than PBL, and the metacognitive abilities of students with IMPROVE and PBL models were either positive or good.